Using simulation to develop business strategy skills of entrepreneurs - Some reflections on a pilot. Issue 3 (June 2021) - Barnaby, Julie; Devins, David; Beech, Nicholas
It is recognized that the value of entrepreneurship education and the recruitment of practising entrepreneurs for such learning programmes can be problematic. This raises an important and challenging issue for universities when they are increasingly being asked to develop the leadership and management capabilities of entrepreneurs. In this account of practice, the authors explore the role for business simulation in the development of existing entrepreneurs' and small business leaders' strategic decision-making skills. The article describes and reflects on a pilot business simulation course, considering the challenges in the planning, the engagement of entrepreneurs and the delivery of the programme. It provides insights into the value of introducing this form of learning experience and exposes the significant challenges associated with engaging small business leaders.